Praktik Packaging Eco-Enzym Dari Kulit Buah Bagi Santriwati Di Panti Asuhan - Larasaty, Nurina Dyah; Alwiyah, Alwiyah; Rahmawati, Mega Sucipto; Kusuma, Idfi Widya (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Food waste such as fruit peels is often found in domestic waste. Fruit peel waste can produce eco-enzymes that have many benefits and do not harm the environment. The utilization of eco-enzymes can be carried out by empowering the community from production to branding. Branding training is conducted to assist the community in improving their quality of life. The methods used in the training include lectures and discussions with participants who are residents of the Putri Aisyiyah Pucang Gading Orphanage. The training is a continuation of the previous community service activities related to the production of eco-enzymes using fruit peel waste in the surrounding environment. The success of the training is evident from the enthusiasm of the orphanage residents for the eco-enzyme and branding materials presented. Monitoring and evaluation are conducted periodically for the coaching of improving the residents' skills in the aspect of product branding. Similar community service programs need to be developed to help communities improve their quality of life.            Keywords: branding; eco-enzym; fruit peels